Study on Reasonable Roadway Position of Working Face under Strip Coal Pillar in Rock Burst Mine - Hengze Yang; Zhongping Guo; Daozhi Chen; Chao Wang; Fuyu Zhang; Zhaowen Du (Shock and Vibration)
It is of great significance to study the reasonable position of mining roadway under strip coal pillar for increasing the stability of mining roadway, reducing the waste of resources, and realizing the safety production of working face. Based on the research background of the working face under the strip coal pillar in Jinqiao Coal Mine of Jining, Shandong Province, through theoretical analysis, similar material simulation experiment, and numerical simulation experiment, the stress distribution law, plastic failure range, and rationality of coal pillar setting in different width sections are systematically studied. Finally, the tailentry of working face is determined at the position of 5 m from the bottom of strip coal pillar to 1308 goaf. During the mining period of 1310 working face, the peak value of side abutment pressure is at the position of 3∼4 m; beyond 25 m in front of the coal wall, the deformation of the surrounding rock on the tailentry surface is small. After entering the advanced support section, the deformation of the two sides is mainly longitudinal crack expansion and local shallow small flakes; however, the roof is complete and stable. Therefore, the selection of tailentry location and coal pillar width has played a good role. The research results of this study can provide some reference for similar mine with similar geological and production technical conditions.